Countries at the Crossroads 2011: An Analysis of Democratic Governance - Freedom House (Rowman & Littlefield Publishers, 2012)
Countries at the Crossroads: An Analysis of Democratic Governance evaluates government performance in seventy strategically important countries from across the globe, including emerging market countries and at-risk states. The in-depth comparative analyses and quantitative ratings—examining Accountability and Public Voice, Civil Liberties, Rule of Law, and Anticorruption and Transparency—serve as a valuable tool for public analysts, educators and students, government officials, and the business community.